Symbolic Representation Of Śiwa Naṭarāja In The Balinese Dance Creativity And Its Impact On Health Maintenance: A Literature Review - Ni Made Ria Taurisia Armayani; I Made Intaran; I Gusti Agung Andriani; I Wayan Ardhi Wirawan (Jayapangus Press, 2021)
This study aims to study the representation of the Śiwa Naṭarāja symbol as the creative spirit of Balinese dance and its implications for the health. This research is designed in an interpretive qualitative type to find answers to the formulation of research problems. This study formulates three findings as answers to research problems. First, the description of Śiwa Naṭarāja symbol in the Indian tradition is contained in Vedic literature and is very developed in the South Indian region. Second, the representation of the symbol Śiwa Naṭarāja is used as a spirit in dance creativity in Balinese society related to elements of Balinese culture which have a very high value for improving the quality of people's lives. Art creativity in the life of Balinese people is closely related to building character which is determined by the aesthetic values ​​contained in the artistic creativity which is able to build refinement of the buddhi (intellect) which in its accumulation can create a better character development. Third, the implication of the expression of rhythm in dance with health care according to Hindu teachings is a strong relationship. The teachings in the Vedic scriptures mandate the activities of dancing, singing and laughing as vehicles for building an atmosphere of joy. This condition has the position of creating positive feeling in order to build a balance of body immunity which at the end has a high bargaining power against disease attacks. Dancing in a social dimension is none other than the framework of cultivating and strengthening brotherhood ties which also have the opportunity to build a healthy atmosphere.